KEHIDUPAN LANSIA YANG DITITIPKAN KELUARGA DI PANTI SOSIAL TRESNA WERDHA KHUSNUL KHOTIMAH PEKANBARU - Siti Aisyah; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
When a person reaches old age, and the children have formed their own families, their responsibilities must let loose on them, and he returned more independent free as in time the beginning of her marriage. Liability parenting, finance, educate and supervise children no longer do. Therefore, elderly issues should concern us all, including government, public institutions and society itself. Increasingly aging person's age they increasingly need a place to shelter and get affection, especially from family. But in reality, many elderly people who are entrusted by the family to social institutions, and even among them there were displaced. The problem in this study ie what factors or issues that the elderly who still have this family entrusted to a nursing home and how social relationships with family, and also what are the joy and sorrow felt by elderly people living in nursing. In this study five elderly people entrusted to PSTW KK Pekanbaru family that is the subject of researchers. The results of this study are the factors of elderly living in nursing because of economic problems, do not want to bother the family, a conflict or misunderstanding with his family, and also because they do not want their families to take care of him anymore. Like it or happy elderly living at home because of the availability of all the facilities of the orphanage and grief or sad being away from family.Keywords: Elderly, Family, Nursing Home